Influencer streamers VS. merchant live streamers: The mediating role of source credibility and authenticity in live-streaming E-commerce on consumer purchase intention - Sudirman, Indrianty; Astuti, Niken Probondani; Basri, Surya Kelana; Syamsuddin, Syamsuddin; Ilyas, Muh Fadhel G Bata (Edelweiss Applied Science and Technology, 2026)
The rapid growth of live-streaming commerce has transformed online retail and intensified the strategic role of streamers. This study aims to compare the effects of influencer streamers and merchant live streamers on consumer purchase intention, while examining the mediating roles of source credibility and authenticity. Using a quantitative design, data were collected from 270 Indonesian Generation Z and Millennial consumers who had purchased products through Shopee Live or TikTok Live during the previous six months. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that both influencer streamers and merchant live streamers significantly enhance perceived source credibility. However, only merchant live streamers exert a strong and significant effect on perceived authenticity. Moreover, neither streamer type directly influences purchase intention. Mediation analysis reveals that authenticity fully mediates the relationship between merchant live streamers and purchase intention, whereas credibility does not mediate the effects of either streamer type. These results demonstrate that authenticity, reflected through sincerity, transparency, and natural interaction, is more influential than credibility in driving consumer purchase intention in live-streaming commerce. This study concludes that host effectiveness depends on distinct psychological mechanisms, suggesting brands and e-commerce platforms should prioritize authentic merchant-hosted live streams strategically.